Finance for micro, small, and medium-sized enterprises in India: Sources and challenges - Charan Singh; Kishinchand Poornima Wasdani (Asian Development Bank Institute (ADBI), 2016)
Finance for micro, small, and medium-sized enterprises (MSMEs) has been a concern for all stakeholders including entrepreneurs, financial institutions, and government organizations. The key objective of the study was to identify various challenges faced by MSMEs in sourcing of finance during different stages of their life cycle. This study is a first-of-its-kind attempt to focus on these aspects. The study further explores whether the financial awareness of MSME entrepreneurs is a major limitation in the identification and utilization of sources of finance. Data was collected through personal interviews using a structured questionnaire from a sample of 85 MSMEs. The survey was conducted mainly in the city of Bangalore covering a wide spectrum of sectors like precision tools, weavers, jewelers, food retailers, metal works, textiles, and book shops. The results reinforce the findings of other studies that utilization of formal sources like banks is significantly small compared with informal sources like personal and family wealth. The study found that the main challenges faced in underutilization of formal sources were inadequacy of collateral assets and lack of financial awareness of entrepreneurs. Based on the conclusion that requirement of finance differs with the life-cycle stage of the MSME, recommendations have been proposed for entrepreneurs, financial institutions, and policy makers.
Keywords: O23; G20; L26; 330; India; SME; small and medium-sized enterprises; microenterprises; finance; loans; capital; start-up; economic growth; firms; banks; financial institutions; financial awareness; sources of finance